Impact of Patient and Procedure Mix on Finances of Perinatal Centres – Theoretical Models for Economic Strategies in Perinatal Centres - Hildebrandt, T.; Kraml, F.; Wagner, S.; Hack, C. C.; Thiel, F. C.; Kehl, S.; Winkler, M.; Frobenius, W.; Faschingbauer, F.; Beckmann, M. W.; Lux, M. P. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: In Germany, cost and revenue structures of hospitals with defined treatment priorities are currently being discussed to identify uneconomic services. This discussion has also affected perinatal centres (PNCs) and represents a new economic challenge for PNCs. In addition to optimising the time spent in hospital, the hospital management needs to define the “best” patient mix based on costs and revenues. Method: Different theoretical models were proposed based on the cost and revenue structures of the University Perinatal Centre for Franconia (UPF). Multi-step marginal costing was then used to show the impact on operating profits of changes in services and bed occupancy rates. The current contribution margin accounting used by the UPF served as the basis for the calculations. The models demonstrated the impact of changes in services on costs and revenues of a level 1 PNC. Results: Contribution margin analysis was used to calculate profitable and unprofitable DRGs based on average inpatient cost per day. Nineteen theoretical models were created. The current direct costing used by the UPF and a theoretical model with a 100 % bed occupancy rate were used as reference models. Significantly higher operating profits could be achieved by doubling the number of profitable DRGs and halving the number of less profitable DRGs. Operating profits could be increased even more by changing the rates of profitable DRGs per bed occupancy. The exclusive specialisation on pathological and high-risk pregnancies resulted in operating losses. All models which increased the numbers of caesarean sections or focused exclusively on c-sections resulted in operating losses. Conclusion: These theoretical models offer a basis for economic planning. They illustrate the enormous impact potential changes can have on the operating profits of PNCs. Level 1 PNCs require high bed occupancy rates and a profitable patient mix to cover the extremely high costs incurred due to the services they are legally required to offer. Based on our theoretical models it must be stated that spontaneous vaginal births (not caesarean sections) were the most profitable procedures in the current DRG system. Overall, it currently makes economic sense for level I PNCs to treat as many low-risk pregnancies and neonates as possible to cover costs.
Keywords: perinatal centres; financing; DRG system; costs; rate of caesarean sections